2019
DOI: 10.1111/hel.12576
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori infection and nonalcoholic fatty liver disease: A systematic review and meta‐analysis of observational studies

Abstract: Background The association between Helicobacter pylori (H. pylori) infection and nonalcoholic fatty liver disease (NAFLD) has been shown in many observational studies, but these conclusions remain controversial. Hence, we performed a meta‐analysis to elucidate the association. Methods A comprehensive search was conducted on relevant studies published from inception to December 31, 2018, in PubMed, EMBASE, and Web of Science databases. Odds ratio (OR) with 95% confidence interval (95% CI) were pooled by random‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 58 publications
3
38
0
1
Order By: Relevance
“…Subsequently, other studies reported a positive association between Hp-I and NAFLD, including those of Yu et al [19], Sumida et al [38], Okushin et al [18], Kim et al [10,27], Zhang et al [21], Chen et al [26], Dogan et al [25], Abdel-Razik et al [24], and Kang et al [11]. Noteworthy, there have been five systematic reviews performed with meta-analysis, all of which revealed a positive association between the pathologies of interest [39][40][41][42][43]. Nonetheless, there are studies showing no association between Hp-I and NAFLD [14,15,19,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, other studies reported a positive association between Hp-I and NAFLD, including those of Yu et al [19], Sumida et al [38], Okushin et al [18], Kim et al [10,27], Zhang et al [21], Chen et al [26], Dogan et al [25], Abdel-Razik et al [24], and Kang et al [11]. Noteworthy, there have been five systematic reviews performed with meta-analysis, all of which revealed a positive association between the pathologies of interest [39][40][41][42][43]. Nonetheless, there are studies showing no association between Hp-I and NAFLD [14,15,19,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have investigated the relationship between NAFLD and H. pylori infection, especially in Asia [18]. However, the conclusions were inconsistent and controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy among previous findings might result from the geographical location, study design, and confounder adjustment. Recently, a systematic review and meta-analysis of 15 observational studies (published between 2013 and 2018) involving 97228 participants showed a robust result that existed a positive association between H. pylori infection and the risk of NAFLD [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has suggested that H pylori is associated with the development of NAFLD 7‐11 . Several meta‐analyses, predominantly from studies of Asian populations, have reported H pylori infection‐NAFLD associations with pooled odds ratios ranging between 1.14 and 1.53 12‐16 …”
Section: Introductionmentioning
confidence: 99%